Family Health Friday Civitas Akademika Kampus IBI Kosgoro 1957 dan Warga Masyarakat Kecamatan Jagakarsa - Filda Angellia; Boy Firmansyah (Jurnal Pengabdian Teratai, 2020)
Technology which is currently developing rapidly requires and guides human life to be more advanced. But technology can also sometimes be a "boomerang" for ourselves both physically and mentally related. Mainly in the field of health, the impact of the latest technology is increasingly in the spotlight and attention because so many people no longer place technology according to its functionality but rather to the primary needs that must be used and included in every aspect of their lives. The phenomenon of "dependence" which can be the most appropriate word on the current human and technological conditions. Especially for women who tend to use technology tools such as smartphones / gadgets to be a primary need that always participates in all daily activities, thus there needs to be extensive knowledge about the impact of technology on health, especially women's health, and of course additional knowledge about women's physical anatomy. complicated, vulnerable and must be maintained. One thing that is no less important is that women are aware of the importance of the health of vital organs of women. In connection with all the things explained above, we feel the need to create persuasive programs that provide knowledge about the dangers of computer technology / gadgets for health, especially women's health, the importance of knowledge about the health of vital organs of women that we pack in our "Family Health Friday" program intended for the IBI-Kosgoro academic community in 1957 and the surrounding community.